Impacts of information and communication technologies on organizational behavior. - Lee, Wei Siew. (Nanyang Technological University, 2008)
This study sought to investigate the impact of Information and Communication Technologies on organizational behavior in Singapore. Results revealed that ICT usage had a significant impact on creativity, information access, commitment and sense of belonging, and organizational structure.